PERANAN PENDIDIKAN DALAM MENGHINDARI PERGAULAN BEBAS ANAK USIA REMAJA - Nadirah, Sitti (Musawa: Journal for Gender Studies, 2017)
The promiscuity of juvenile delinquency is increasingly showing a very alarming increase. This paper examines the role of education in avoiding the promiscuity of adolescent children. With education it will create the formation of character. With the character of teenage children will "lead" themselves to do something right and not do something that is not true. This character becomes the determinant of whether adolescents are able or not to adjust to the diversity of situations that it faces, especially to avoid promiscuity. In addition to the realization of Gender-based education, women can earn non- loyal equality. Which in the long term can improve the protection, service and welfare of vulnerable women as the most disadvantaged party in free sex among adolescents.